Effectiveness of Autologous Stem Cell Therapy for the Treatment of Lower Extremity Ulcers: A Systematic Review and Meta-Analysis. Issue 11 (March 2016) - Jiang, Xupin; Zhang, Hengshu; Teng, Miao
Abstract : Abstract: Primary studies in animal models and humans have suggested the therapeutic potential of autologous stem cell for treating chronic lower extremity ulcers. However, the results of pilot randomized controlled trials (RCTs) in humans have been inconsistent. A meta-analysis of RCTs was performed to evaluate the role of autologous stem cell-based therapy for lower extremity ulcers. Studies were identified during a systematic search of Medline, Embase, Cochrane's library, and references cited in related reviews and studies. Studies were included if they were RCTs published in English, recruited patients with lower extremity ulcers who were assigned to either a group for the topical therapy with autologous stem cells, and reported data regarding the healing of the ulcers. Relative risks (RRs) for healing rate and standardized mean differences (SMDs) for the changes in the mean sizes of ulcers were evaluated with a random-effects model. Overall, autologous stem cell-based therapy was associated with better healing of lower extremity ulcers (12 comparisons, 290 patients, RR for partial healing = 3.07, 95% confidence interval [CI] = 1.14–8.24, P = 0.03; RR for complete healing = 2.26, 95% CI = 1.48–3.16, P < 0.001) with little heterogeneity ( I 2 = 0%). Moreover, autologous stem cell-based therapy was associated with a greater reduction in mean ulcer size (SMD = −0.63, 95% CI = −1.03 to −0.22, P = 0.002). Subgroup analyses indicated that stem cells from peripheral blood and bone marrow seemed to exert similar beneficial effects on the healing of ulcers. Stem cell therapy was not associated with any increased risks for adverse events. The optimized sources, amounts, and delivery methods of stem cell -based therapy for patients with chronic lower extremity ulcers need to be determined, and the long-term effects of stem cell-based therapy on clinical outcomes need further exploration. Autologous stem cell-based therapy is effective and safe for improving the healing of chronic lower extremity ulcers and large-scale RCTs are needed to confirm our findings.